Study on Influencing Factors of Casing Thread Corrosion and Anti - Rust Mechanism of Stored Grease - WANG Xian - hui, CHI Wei, WANG Zhao - kun, CHU You - shuang, TIAN Ning - ning (Cailiao Baohu, 2021)
Under the influence of water, oxygen, electrolyte, high temperature and other conditions in the external environment, the electrochemical reactions on the metal surface is the root cause of casing thread corrosion. The effects of thickening agents, additives and external conditions on the rust resistance of casing thread storage grease made from high alkali value calcium sulfonate complex were studied by salt spray test in laboratory and outdoor investigation in order to prevent early casing failure caused by rust. Results showed that the key factors to determine the anti - rust effect of stored grease were the properties of thickening agent, such as adsorption, solubilization, acid neutralization etc. The further addition of antirust single agent or complex agent would have a certain enhanced and synergistic effect on the antirust property of stored grease. According to the production and application status of oil casing in China, the research on corrosion causes of casing threads and anti - rust mechanism of stored grease is of great value and significance.